CREATION AND VALIDATION OF Q-DIO, AN INSTRUMENT FOR RATING THE QUALITY OF NURSING DOCUMENTATION - LITERATURE REVIEW - Dagmar Šerková; Jana Marečková (University of Ostrava, 2018)
Aim: To summarize relevant information on the creation and validation of the Quality of Nursing Diagnoses, Interventions and Outcomes (Q-DIO) assessment instrument. Design: A literature review. Methods: To search for studies, the first two steps of a standard evidence-based healthcare approach were used: 1) formulation of a search question and 2) structured documented search including assessment of the relevance of abstracts and full text of studies to the search question and inclusion criteria. In relevant studies, the level of evidence was evaluated using the Joanna Briggs Institute categories. Results: Out of 212 results of two-step search in scholarly databases and grey literature sources, only three literature resources were relevant. The newly developed Q-DIO instrument was assessed by its authors using content and face validation (100% consensus of experts and 88.25% agreement), intrarater (r = 0.98; p < 0.0001; κ = 0.95; p < 0.0001) and interrater reliability (r = 0.99; p < 0.0001, κ = 0.95; p < 0.0001) and internal consistency of the concepts of the instrument (Cα = 0.83; Cα = 0.98; Cα = 0.90; Cα = 0.99). Item analysis was carried out to determine both difficulty and discriminative validity of the items. Conclusion: Q-DIO was by the authors marked as valid assessment instrument by its authors. However, since the assessed instrument items are formulated without identifying currently valid NNN nomenclature terminology, they should be specified prior to a particular assessment of the quality of nursing documentation. Keywords: item analysis, literature review, Q-DIO, quality of documentation, reliability, validation.